Profitability of Maize and Groundnut Crop Production under Different Irrigation Systems with Varied Irrigation and Nitrogen Level Application in Southern India - , Aminullah Noorzai; , K. Suresh; , A.S. Subbarao; , K.A. Kumar; , K.P.C. Reddy; , P. Satish (Archives of Current Research International, 2024)
An experiment was conducted to study the effects of irrigation systems, irrigation, and N levels on the economics of maize and groundnut during 2021-22 and 2022-23 at the College Farm, College of Agriculture, Rajendranagar, PJT Agricultural University, Hyderabad. The experiment consisted of 18 treatment combinations (3 irrigation systems as the main plot, 3 irrigation levels as the sub-plot, and 2 nitrogen levels as the sub-sub-plot) in a split plot design replicated thrice. The experiment revealed that among irrigation systems, irrigation, and N levels in both crops (maize and groundnut) significantly higher gross returns, net returns, and BCR were recorded with M2 (sub-surface irrigation system), S1 (1.2 Epan; IW/CPE) and N1 (100 percent RDN). In both crops, the interaction between irrigation system and irrigation levels (M x S) revealed significantly higher returns and BCR with sub-surface drip irrigation levels@ 1.2 Epan & 0.9 Epan ratios (M2S1 and M2S2) followed by surface drip irrigation levels @ 1.2 Epan & 0.9 Epan ratios (M1S1 and M1S2), surface irrigation @ 1.2 IW/CPE ratio (M3S1). In contrast, surface irrigation @ 0.6 IW/CPE ratio (M3S3) resulted in the least returns and BCR during both the years. The interaction effects of irrigation systems and N levels (M x N), irrigation, and N levels (S x N) were non-significant in the groundnut crop whereas they were significant in maize crop. The M2N1 recorded significantly higher mean gross returns (₹. 1,46,852 ha-1), net returns (₹. 90,960 ha-1), and BCR (2.62) whereas M3N2 recorded the lowest mean gross return (₹. 97,052 ha-1), net return (₹. 45,305 ha-1) and BCR (1.87). Among S x N interaction effects, the S1N1 (1.2 Epan; IW/CPE with 100 percent RDN) resulted in significantly higher gross returns (₹. 1,44,385 ha-1), net returns (₹. 89,256 ha-1) and BCR (2.61) followed by S2N1. In contrast, S3N2 resulted in significantly least returns and BCR. The interaction effects of irrigation systems, irrigation, and N levels (M x S x N) were non-significant in the groundnut crop while showing a significant impact on the economics of maize. The sub-surface irrigation system (M2) with 1.2 Epan (S1) and 100 percent RDN (N1) recorded significantly higher mean gross returns (₹. 1,58,749 ha-1), net return (₹. 1,10,243 ha-1) and BCR (2.82) followed by M2S2N1 (₹. 1,56,106 ha-1, ₹. 1,14,542 ha-1 and 2.79), M1S1N1 and M1S2N1 while M3S3N2 (surface irrigation system with 0.6 IW/CPE and 75 per cent RDN) recorded least mean gross returns (₹. 65,253 ha-1), net returns (₹. 14,106 ha-1) and BCR (1.28) thus making it the least remunerative among all treatment combinations studied.